The Influence Of Online Advertising On Increasing Sales Of Culinary Product Using Facebook Social Media as a Moderating Variable - Kurniawan, Agus (Jurnal Ilmiah Raflesia Akuntansi, 2024)
Social media is currently the most widely used promotional tool and place to communicate because it has a very significant impact on business development because it has advantages including the number of users and does not require costs to create an account on a social media. One of the social media that is still in demand today and has many users is Facebook. and the Facebook application itself is easily accessible to any group, does not limit age and is easy to reach. The objectives of the research are (1) The influence of online advertising in increasing sales of culinary products in Berasan Makmur Village, Mesuji Regency , (2) The ability of Facebook social media as a moderating variable in the influence of online advertising in increasing sales of culinary products in Berasan Makmur Village, Mesuji Regency , and (3) Providing an overview of the activities of culinary entrepreneurs who advertise on Facebook social media. This research uses quantitative research type. Where the researcher used primary data obtained from distributing questionnaires to 23 respondents using the Purposive Sampling Technique on students of the Sharia Business Management study program in Bandar Lampung. Namely, culinary sellers via Facebook social media in Berasan Makmur Village, Mesuji Regency